Inotropes for preterm babies during the transition period after birth: friend or foe?. Issue 6 (17th August 2017) - Rabe, Heike; Rojas-Anaya, Hector
Abstract : During the transition to extrauterine life, preterm infants are at high risk of developing circulatory failure. Currently, hypotension is used as major diagnostic criteria for starting treatments such as fluid boluses, inotropes or steroids. Most of these treatment options have not been studied in large randomised controlled trials for efficacy and safety and are under discussions. A wide variety in their use is reported in the literature and clear evidence about which inotrope or other treatment should be preferred is lacking. In addition, there is ongoing debate about the appropriate threshold values for blood pressure. Other diagnostic measures for poor circulation are functional echocardiography, near-infrared spectroscopy, capillary refill time, base excess and serum lactate. Large randomised controlled trials for the use of dopamine and dobutamine in preterm infants <32 weeks gestation are under way to fill the knowledge gaps on the assessment of circulatory compromise and on efficacy and safety of the studied age-appropriate drug formulations.